TOWARDS AN INTEGRATED MODEL OF COMMUNICATIVE COMPETENCE IN BUSINESS EDUCATION : THE ROLE OF BILINGUAL COMPETENCY AND PAIR INTERACTION - Suhartina R (PT. Jurnal Center Indonesia Publisher, 2026)
Communicative competence has become an essential competency for business education students in response to the growing demands of multilingual, multicultural, and technology-driven workplaces. However, previous studies have generally examined bilingual competency, collaborative learning, and communicative competence as separate constructs, providing limited understanding of their integrated relationships. This study aimed to develop an Integrated Communicative Competence Model for business education through the synthesis of previous empirical studies and recent international literature. A conceptual research design employing an integrative evidence synthesis approach was used to analyse empirical findings on bilingual competency, pair interaction, communicative competence, and professional readiness. The synthesis demonstrates that bilingual competency provides the linguistic and intercultural foundation for effective communication, while pair interaction functions as a collaborative learning mechanism that strengthens authentic communication practices. The interaction of these dimensions enhances communicative competence, which subsequently improves students' professional readiness and graduate employability in multilingual business environments. The proposed model contributes to communication studies by integrating bilingual competency and collaborative learning into a unified conceptual framework and provides practical guidance for curriculum development and communication-oriented learning in business education.